Ang pagtuklas: Camille's journey to Filipinization: a children's book - Castillo, Alyssa Karol R. (Animo Repository, 2016)
This post-defense final report on the thesis project, Ang Pagtuklas: Camille's Journey to Filipinization , aims to tackle the overall production of the said project- from topic proposal, research on review of related literature, production details, and even defense proper, as well as panelists comments and suggestions. This post-defense final report also includes necessary information as the proponents note down certain details that could serve as proper guidance to future thesis proponents-whom of which might also possibly write a children's book for their thesis project.